Trisomy 14 mosaicism in a 2 year old girl. Issue 1 (February 1986) - Petersen, M B; Vejerslev, L O; Beck, B
Abstract : Trisomy 14 mosaicism with 6% trisomic cells in blood and 16% in skin fibroblasts was found in a 2 year 2 month old girl with mild psychomotor retardation, craniofacial dysmorphism, pectus carinatum, curved fifth fingers, retarded bone age, and signs of an ASD. These findings are consistent with the previously reported cases of trisomy 14 mosaicism and support the suggested existence of a distinctive syndrome. Non-disjunction studies showed that the extra chromosome 14 originated from either a second paternal meiotic error or an early mitotic error.